THEOLOGICAL INTERPRETATION OF MUTASHABIH VERSES IN IBN KATHIR’S AL-QUR’AN AL-‘AZIM AND ITS IMPLICATIONS FOR SUNNI THEOLOGICAL DISCOURSE: Corak Teologis Penafsiran Ayat-Ayat Mutasyabih dalam Tafsir Al-Qur’an Al-‘Azhim Karya Ibnu Kaṡir dan Implikasinya terhadap Diskursus Teologi Sunni - Pendi Nurul Azmi (Tunas Harapan Ummat Foundation, 2026)
This study examines the interpretation of the verses concerning the Divine Attributes (āyāt al-ṣifāt) in Tafsīr al-Qur’ān al-‘Aẓīm by Ibn Kathīr, focusing on the theological tendency reflected in his exegesis. This research is motivated by differing views regarding Ibn Kathīr’s theological position within the discourse of Ahl al-Sunnah wa al-Jamā‘ah. Some scholars place him close to the Ash‘arite tradition, while others argue that his exegetical method more accurately reflects the Atharite approach. These differing assessments make Ibn Kathīr’s interpretation of the verses concerning the Divine Attributes an important subject of academic investigation in order to obtain a more objective understanding of his theological orientation. This study employs a qualitative library research method. The primary source of data is Tafsīr Al-Qur’ān al-‘Aẓīm by Ibn Kathīr, while supporting data are drawn from various works on Qur’anic exegesis, ‘Ulūm Al-Qur’ān, and theological literature representing both Ash‘arite and Atharite thought. The analysis is conducted through descriptive-analytical and comparative methods, examining Ibn Kathīr’s interpretations of several verses concerning the Divine Attributes, including istiwā’ (rising above the Throne), kalām Allāh (the Speech of Allah), wajh Allāh (the Face of Allah), ru’yatullāh (the Beatific Vision), and jā’a Allāh (the Coming of Allah), and comparing them with the methodological characteristics of the two theological schools. The findings indicate that Ibn Kathīr’s interpretation of the verses concerning the Divine Attributes is generally closer to the Atharite approach. This is evident in his tendency to affirm Allah’s attributes as mentioned in the revealed texts without resorting to figurative interpretation (ta’wīl), while rejecting takyīf (specifying the modality), tamthīl (likening Allah to His creation), ta‘ṭīl (negating the attributes), and taḥrīf (distorting their meanings). In his interpretations of the verses concerning istiwā’, kalām Allāh, ru’yatullāh, and jā’a Allāh, Ibn Kathīr consistently follows the methodology of the Salaf by maintaining the apparent textual meanings in a manner befitting Allah’s majesty. Although, in interpreting wajh Allāh, he occasionally explains it as referring to Allah’s Essence (dhāt Allāh), this is insufficient to alter the overall tendency of his methodology. Therefore, this study concludes that Ibn Kathīr’s theological orientation in interpreting the verses concerning the Divine Attributes is closer to Atharism than to Ash‘arism. This finding demonstrates that Tafsīr Ibn Kathīr represents one of the significant examples of the Salaf-oriented exegetical approach within the tradition of Ahl al-Sunnah wa al-Jamā‘ah.